2011
DOI: 10.1519/jsc.0b013e3181f11c41
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Combined Exercise Training in Adolescents Who Are Overweight Or Obese With Intellectual Disability: The Role of Training Frequency

Abstract: Data about effects of exercise training in adolescents with intellectual disability (ID) are very limited. This study investigated the effect of 2 different frequencies of the same intensity and total training volume of combined exercise training on indices of body composition, physical fitness, and lipid profile in overweight and obese adolescents with ID. A total of 45 overweight and obese adolescents with ID aged 14-22 years with a total IQ 45-70 received combined exercise training 3 times a week (CET3) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 22 publications
7
60
0
1
Order By: Relevance
“…An interesting study by Elmahgoub et al (2011) investigated the influence of physical training on obesity in intellectually disabled teenagers who exercised 2 or 3 or more times a week. The research showed significant improvement in physical fitness and beneficial a influence of the exercises on obesity and weight loss.…”
Section: Resultsmentioning
confidence: 99%
“…An interesting study by Elmahgoub et al (2011) investigated the influence of physical training on obesity in intellectually disabled teenagers who exercised 2 or 3 or more times a week. The research showed significant improvement in physical fitness and beneficial a influence of the exercises on obesity and weight loss.…”
Section: Resultsmentioning
confidence: 99%
“…Information obtained from the respondents consisted of demographic, social, and health related factors; i.e., age, education, employment body mass index (BMI), sun exposure, daily physical activity (low or moderate level) (9) , passive smoking (mixture of side stream smoke emitted by lit cigarettes and mainstream smoke exhaled by smokers) (10) and past history of back trauma.…”
Section: Sampling Techniquementioning
confidence: 99%
“…Some of these activities have produced weight loss in various samples with ID including amongst adults (Wu et al 2010), children (Singh et al 2008) as well as individuals with Down syndrome (Rimmer et al 2004a). Certain changes were statistically significant (Elmahgoub et al 2009;Elmahgoub et al 2011;Ordonez et al 2006) while others were maintained at 6-month follow-up (Wu et al 2010). Researchers have documented positive change in waist circumference (Elmahgoub et al 2009(Elmahgoub et al , 2011 and also BMI (Moss 2009) including amongst individuals with Down syndrome (Rimmer et al 2004a).…”
Section: Behavioral Interventionsmentioning
confidence: 99%